Learning to teach Biology to pre-service teachers: a self-study - Khoza, Hlologelo Climant (My University, 2020)
Due to the lack of formal training for those who wish to be teacher educators in South Africa and around the world, I did on-the-job training and used a self-study methodology to explore how I, as a novice teacher educator, can learn to teach biology to pre-service teachers. I viewed learning as the “coming-to know” process facilitated by constructive interactions and observations in a community of practice. I was the main participant. The other participants were my 135 pre-service teachers whom I was teaching in the course and six biology teacher educators who were working in the same department. I collected data through journaling, observations of and discussions with the experienced biology teacher educators, audio-and video-recordings of my lectures, discussions with critical friends and interviews with students. Narrative text analysis was used to draw insights. The student interviews and discussions with experienced teacher educators were analysed using both inductive and deductive approaches. This study showed that one can learn to teach pre-service teachers in systematic ways and approaches. These systematic ways include reflecting on experiences accumulated over the years, observing experienced teacher educators as they teach and discussing with them, teaching a topic for a short period with the help of the experienced teacher educators, moving from general observations and discussions to focusing on particular aspects of practice and planning and teaching a full module. In this thesis, I demonstrate how these approaches helped me learn and the knowledge and skills I gained in the process. The findings in this study showed that a novice teacher educator can learn about teaching practice by engaging in critical reflection based on their students’ feedback. I further demonstrate that, for this reflection and learning to be meaningful, the feedback has to be sought continuously from the students being taught. Using the findings from this study, I proposed a model or framework for learning that novice teacher educators can adopt not only to acquire practices of teaching biology to pre-service teachers but also to track their learning. Recommendations for future research are also highlighted
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020
Keywords: Biology--Study and teaching; Teachers--Training of